A Survey of Medicinal Plants around Kedarnath Shrine of Garhwal Himalayas - Mehrotra, B. N. (Indian Forester, 1979)
A survey of medicinal plants growing in and around the holy shrine of Kedarnath has been undertaken. The present paper describes 68 medicinal plants found growing in the area ranging in altitude between 2700 and 4200 m with two alpine lakes. The area abounds in a number of important medicinal plants, such as aconitum heterophyllu (Atis), Nardostachys jatamansi (Jatamansi), Orchis latifolia (Salep), Picrorhiza Kurrooa (Katki), Podophyllum hexandrum (Indian podophyllum), Rheum webbianum (Indian rhubarb), Taraxacum officinale (Taraxacum), Valeriana hardwickii (Valerian), Viola biflora and V. serpens (Banafea). The medicinal plants are listed alphabetically with their family and a brief account of their habit, habitat, occurrence and altitude. The month and year of collection, local names, wherever available, and uses have also been given. Specimens are preserved in the herbarium of the Central Drug Research Institute, Lucknow. Suggestions have also been made for the protection of the natural wealth from indiscriminate exploitation.